2022
DOI: 10.3390/biology11040599
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and Metabolic Potential of the Candidate Phylum SAR324

Abstract: The bacterial SAR324 cluster is ubiquitous and abundant in the ocean, especially around hydrothermal vents and in the deep sea, where it can account for up to 30% of the whole bacterial community. According to a new taxonomy generated using multiple universal protein-coding genes (instead of the previously used 16S rRNA single gene marker), the former Deltaproteobacteria cluster SAR324 has been classified since 2018 as its own phylum. Yet, very little is known about its phylogeny and metabolic potential. We do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 73 publications
(106 reference statements)
1
10
1
Order By: Relevance
“…In deep waters of the eastern tropical South Pacific, taurine uptake and desulfonation genes are dominated by SAR324 bacteria and the gammaproteobacterial ARCTIC96BD-19 clade (Landa et al 2019 and references therein), suggesting that sulfite generation from taurine could be further oxidized to sulfate by these groups (Callbeck et al 2021). SAR324 bacteria have recently been classified into multiple subclades inhabiting the entire water column (Boeuf et al 2021, Malfertheiner et al 2022), but the highest abundances are found in meso-and bathypelagic waters (Ghiglione et al 2012, Malfertheiner et al 2022). SAR324 bacteria are metabolically diverse, and subclades present in the deep ocean share genomic features of a mixotrophic lifestyle, including sulfur-based chemolithoautotrophy and C1 compound metabolism (Swan et al 2011, Boeuf et al 2021.…”
Section: Substrate Uptake Strategies Of Marine Prokaryotes: Is More R...mentioning
confidence: 99%
“…In deep waters of the eastern tropical South Pacific, taurine uptake and desulfonation genes are dominated by SAR324 bacteria and the gammaproteobacterial ARCTIC96BD-19 clade (Landa et al 2019 and references therein), suggesting that sulfite generation from taurine could be further oxidized to sulfate by these groups (Callbeck et al 2021). SAR324 bacteria have recently been classified into multiple subclades inhabiting the entire water column (Boeuf et al 2021, Malfertheiner et al 2022), but the highest abundances are found in meso-and bathypelagic waters (Ghiglione et al 2012, Malfertheiner et al 2022). SAR324 bacteria are metabolically diverse, and subclades present in the deep ocean share genomic features of a mixotrophic lifestyle, including sulfur-based chemolithoautotrophy and C1 compound metabolism (Swan et al 2011, Boeuf et al 2021.…”
Section: Substrate Uptake Strategies Of Marine Prokaryotes: Is More R...mentioning
confidence: 99%
“…Overall, these data suggest that SAR324 contributes to sulfur cycling via the dsr pathway in a variety of niches across the globe. Further, dsr - encoding SAR324 are phylogenetically diverse, suggesting that sulfur cycling in SAR324 is more widespread than has previously been suggested (44).…”
Section: Resultsmentioning
confidence: 96%
“…With only a handful of these genomes being described in literature, it has remained unclear if these unique gene combinations are a biological phenomenon (as opposed to mis-assembly) and, if so, why might these phyla carry them.Inspired by these discoveries, we delved further into our exploration, zeroing in on an intriguing phylum: Candidate Phyla SAR324, hereafter referred to as SAR324. Thriving in diverse marine environments, SAR324's metabolically versatile nature adds complexity to its role in sulfur cycling (42)(43)(44)(45)(46). Not only do select SAR324 genomes exhibit unique dsr gene combinations, but their dsrA sequences have been found to stand apart phylogenetically from other bacterial sulfur oxidizers and reducers (45).…”
mentioning
confidence: 99%
“…The SAR324 clade (previously known as Marine Group B, as a member of the Deltaproteobacteria, and now as a candidate phylum) is found throughout the global oceans but predominantly in bathypelagic waters (Haroon et al 2016; Boeuf et al 2021; Malfertheiner et al 2022). Nevertheless, the SAR324 clade has also been observed as a significant member of planktonic estuarine and coastal communities, for example in the Amazon River plume, as well as in other estuaries and coastal sediment (Satinsky et al 2017; Boeuf et al 2021; Malfertheiner et al 2022). Within our coastal nGoM samples, the SAR324 clade was the 12th most abundant taxon (ASV6) and was present in all samples with a salinity > 2 ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“…ASV6 and others (e.g., ASV328, ASV653, ASV690) classified as SAR324 imply a brackish-adapted subclade within SAR324 that warrants further investigation ( Table S1 : 0.2-2.7 µm RA). Organisms within the SAR324 clade possess the potential for flexible metabolic capacity such as the ability to utilize complex organics, light, as well as fix carbon via the Carbon-Benson-Basson cycle (Malfertheiner et al 2022; Jurdzinski et al 2023), which may facilitate their ecological and evolutionary transition to brackish environments. Previous phylogenomic studies on cross-biome transitions found that plasticity may be a hallmark feature of brackish-adapted organisms (Jurdzinski et al 2023).…”
Section: Discussionmentioning
confidence: 99%